If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -3x + 2x = 7766 Combine like terms: 12x + -3x = 9x 9x + 2x = 7766 Combine like terms: 9x + 2x = 11x 11x = 7766 Solving 11x = 7766 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '11'. x = 706 Simplifying x = 706
| Y=6x^2+11x+3 | | 2.50x+3.50(8-x)=23.00 | | 5x+12=50 | | 0=30-3x+3x^2 | | 8(x-6)=24 | | 4x+8x+4.345= | | f(x)=x^3+2x^2+5 | | 9x-3=2x+53 | | 2xn+12=52 | | 9x-3=2x | | 2x^3-3x^2-20=0 | | 3+5z-7+2yz-8z= | | -4x-15=37 | | 53x-1=125 | | y-9=(6/5)(x+6) | | 9x-x-x+x=648 | | 24x^2+x+3=0 | | .5(f+h)=c+d-3f | | 2x^2-10x+3=2x(x-5) | | 220=2(w-40)+2w | | f(x)=x^2-2x-2 | | 40-4x=108 | | 7.95x=-6.5+14 | | 1(9.2)+.2(x)=64(1+x) | | 12x-1=4x+15 | | .5n+n=3 | | 2x+4x=-2 | | 5x-60-3x=3(-4x+15)-2 | | 122=2x+2(6x-16) | | f(x)=x^2-x+1 | | -x=99 | | f(x)=(x-3)2 |